Sample preparation in analytical peptidomics: It's all about timing - Amélie Descamps; Bart De Spiegeleer; Evelien Wynendaele; Petar Naumovski; Anton De Spiegeleer (Talanta Open)
Identifying reliable biomarkers for rapid and accurate disease detection, prognosis, and treatment is becoming increasingly important. Peptides have recently emerged as a promising group in this domain. However, detailed information about their short-term analytical stability remains limited, from sample collection to the obtention of stabilized aliquots for UPLC-MS/MS analysis. This study assessed the impact of time-dependent sample preparation from blood and saliva on the stability of 17 structurally diverse quorum sensing peptides, a class of biologically active peptides. A significant time effect was observed, defined as the percentage ratio of slow versus rapid sample preparation under clinically relevant conditions. The average (± SEM) stability of the investigated peptides was found to be 55 (±19) % in blood and 32 (±22) % in saliva. A more detailed analysis of the kinetic profiles of five selected peptides revealed that metabolization (notably in blood) and adsorption (notably in saliva) were the primary factors influencing the observed time effect. The implications of these findings on detection limits were also discussed. This study highlights the critical importance of precise timings in analytical peptidomics procedures.